Beckett's Metatheatrical Philosophy: A postmodern Tendency Regarding Waiting for Godot and Endgame - Keshavarz, Marzieh (Richtmann Publishing, 2012)
There are so many controversial debates over the features of Beckett's dramatic works that surpass the previous models ofliterary plays. Andrew K. Kennedy (1991) asserts that